1993
DOI: 10.1002/cjce.5450710103
|View full text |Cite
|
Sign up to set email alerts
|

Devolatilization and char burning of coal particles in a fluidized bed combustor

Abstract: Devolatilization and char burning were studied in an electrically heated bench-scale fluidized-bed reactor at 750 to 900°C bed temperature, gas oxygen mole fractions ranging from zero to 0.21, superficial gas velocities from 0.3 to 0.7 m/s and coal particle diameters 5 to 3.5 mm. The coals investigated include lignite, bituminous and anthracite. The coal devolatilization and char burning times, H/C ratio histories, and particle fragmentation were measured. Statistical correlations with the operating variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 11 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…It can be seen that the fluidization velocity does not play a noticeable role on devolatilization time of the oil sludge pellet in air atmosphere. This is consistent with the study by Jia et al [23], who undertook experiments on pyrolysis and combustion of several coals in FB reactor, and found that superficial gas velocity play a little role on release and burnout of volatiles.…”
Section: Influence Of Fluidization Velocity On Devolatilizationsupporting
confidence: 90%
“…It can be seen that the fluidization velocity does not play a noticeable role on devolatilization time of the oil sludge pellet in air atmosphere. This is consistent with the study by Jia et al [23], who undertook experiments on pyrolysis and combustion of several coals in FB reactor, and found that superficial gas velocity play a little role on release and burnout of volatiles.…”
Section: Influence Of Fluidization Velocity On Devolatilizationsupporting
confidence: 90%
“…There are very few reports in the literature on devolatilization time in oxygen-enriched air [46,56,57]. A summary of these results is presented in Table IV.…”
mentioning
confidence: 71%
“…Jia et al discussed the importance of studies on larger coal particles and reported devolatilization times of coal of various sizes up to 36 mm. However, a review on devolatilization of coals in fluidized beds by Borah et al points out that there are only a few devolatilization studies in conventional FB combustors that focus on larger particles as used in commercial units.…”
Section: Introductionmentioning
confidence: 99%
“…The use of large (mm-sized) fuel particles can also be beneficial in the CLC systems for the following other reasons: (i) reduction in auxiliary power consumption by cutting down energy usage in pulverizing fuel particles 20 and the power consumption reduces further upon using heavily fragmenting high-carbon coals under FB conditions; (ii) use of large coal particles aids in slow release of volatiles and other combustible gases, resulting in reduced levels of uncombusted gases at the exit of fuel reactor (thus cutting down the oxygen requirement for oxygen-polishing step) and also avoiding additional requirement of oxygen carrier inventory in the system. Jia et al 21 discussed the importance of studies on larger coal particles and reported devolatilization times of coal of various sizes up to 36 mm. However, a review on devolatilization of coals in fluidized beds by Borah et al 22 points out that there are only a few devolatilization studies in conventional FB combustors that focus on larger particles as used in commercial units.…”
Section: Introductionmentioning
confidence: 99%